Hubungan Resiliensi Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Skizofrenia Di Rumah Sakit Jiwa Provinsi Kalimantan Barat - Deni Setiyawan; Florensa; Dewin Safitri (STIKes YARSI Pontianak, 2025)
Background: Schizophrenia is a chronic illness that requires long-term and continuous management. In an effort to maximize the recovery process, the role of family is crucial in the care of schizophrenia patients. One important task of the family is to attend to the patient's needs, such as taking medication regularly. Objective: This study aims to analyze the relationship between family resilience and medication adherence in schizophrenia patients. Methods: This research is a quantitative study using a descriptive-analytic approach with a cross-sectional design. The sample size of 96 respondents consists of patients and their families. The sampling technique used is purposive sampling. The data collection method used is a questionnaire. The statistical test used is the Gamma Test. Results: The study showed a significant relationship between family resilience and medication adherence in schizophrenia patients (p = 0.004) with a moderate correlation and a positive direction (r = 0.453). Conclusion: Family resilience is essential in the process of caring for patients with schizophrenia, where each family member can provide positive motivation, support, and work together to overcome any difficulties or problems experienced by the patient, including taking medication regularly. The hospital, thru the Keswamas, is advised to always educate the public about the importance of family resilience in providing maximum care for schizophrenia patients to prevent relapse.